Changes in the consistency limits of clay soils with fiber reinforcement - Aslan Topçuoğlu, Yasemin; Gürocak, Zülfü (Gumushane University, 2024)
There are many methods used to improve the engineering properties of clays. Fiber reinforcement method, which has become increasingly common in recent years, has also been added to these traditional methods. In this method, which has many advantages over traditional methods, fiber types such as basalt, glass and polypropylene are used and the engineering properties of the soils used in the filling can be improved. With the use of fiber in soil reinforcement being used intensively in engineering applications recently, there is also a significant increase in scientific studies on this subject. In the studies carried out so far using fiber reinforcement, changes in the strength and swelling properties of the soil have mostly been examined. However, there are very few studies examining the effect of fiber on the consistency limits of the soil. Since the change in consistency limits affects soil stability, it is very important to determine the changes that occur with fiber reinforcement. More scientific studies and databases are needed to understand the fiber-soil interactions, changes in the geotechnical properties of the soil and the mechanism of these changes as a result of fiber use. This study examined changes in liquid and plastic limit values by adding different amounts of basalt fiber to kaolin clay. For this purpose, the changes in the liquid limit, plastic limit and plasticity index values of the clay samples prepared by adding 24 mm long basalt fiber to kaolin clay at the rates of 0.25, 0.50, 1.00, 1.50, 2.00, 2.50 and % 3.00 were examined. According to the results of the study, with basalt fiber reinforcement, there was a decrease in the liquid limit values of kaolin clay and an increase in the plastic limit values. The basalt fiber ratio with the highest decrease in the liquid limit and the highest increase in the plastic limit in reinforced kaolin clay was determined as 2.00 %. As a result of these changes in liquid and plastic limit values, the plasticity index of kaolin clay decreased and due to this decrease, kaolin clay became more stable. © 2024, Gumushane University. All rights reserved.
Fiber takviyesi ile killi zeminlerin kıvam limitlerinde meydana gelen değişimler
Keywords: Basalt fiber; Consistency limit; Kaolin; Soil reinforcement